Successful use of dupilumab for the treatment of atopic dermatitis on the genitals, a neglected anatomical site. (1st January 2022) - Paolino, G.; Sernicola, A.; Di Nicola, M. R.; Foti, A.; Brianti, P.; Vaira, F.; Grieco, T.; Mercuri, S. R.
Abstract: Atopic dermatitis (AD) is a chronic inflammatory disease that may involve any cutaneous site; involvement of the genital area may greatly impair patients' quality of life but, as the inspection of genitals is not usually conducted during the routine physical examination of patients with AD, the genital presentation of AD is frequently neglected and under‐reported. We decided to evaluate the incidence of genital AD in patients with moderate–severe AD and the relative response to anti‐interleukin (IL)‐4/IL‐13 dupilumab. In our study, a high incidence of genital AD emerged but the use of dupilumab allowed a generalized improvement.